(untitled) (Hungarian Journal of Industry and Chemistry, 2010)
For correct operation of the permanent magnet synchronous motors is essential the knowledge of the rotor position, which is usually given by Hall-sensors, encoders or resolvers. The aim of the present work is to set up such a general motor model, which takes into consideration the anisotropies in the magnetic structure of the motor.